The influence of knowledge sharing on transfer of training: Test of a model - Baharim, Shahril (2008)
The role of training has evolved from a focus on programs to a broader focus on learning, creating and sharing knowledge to improve employees’ performance and help meet business needs and challenges. Although HRD researchers recognise the importance of knowledge sharing in understanding transfer of training, empirical research examines the relationship between this variable and post-training behaviour has been neglected. Thus, this study examined the relationship between knowledge sharing and trainees’ motivation to transfer their training (trainees’ desire to use training on the job) once they return to work. Using Holton’s (1996) model as a framework, structural equation analysis revealed that the extent to which trainees share the learned knowledge and skills had an indirect influence on their motivation to transfer their training on the job via its relationship with content validity (training content to accurately reflect job requirements), personal outcomes-positive (applying training on the job leads to outcomes that is positive for the trainees), feedback (indicators from an organisation about an individual’s job performance) and personal capacity for transfer (the extent to which trainees have the time, energy and mental space to make changes required to transfer learning to the job). The findings suggest that trainees should be encouraged to share the learned knowledge and skills with others in the workplace. At the same time, HRD managers strive to stimulate a knowledge sharing culture in organisations and give recognition for those who share their knowledge. This, in turn, provides greater return on investment on training course implementation.